Evaluation of Information Reliability and Quality of YouTubeTM Videos about Teeth Whitening - Özhan Yağci; Muhammet Fidan (Current Research in Dental Sciences)
Objective: The objective of this study was to assess the reliability and quality of information presented in YouTubeTM videos related to teeth whitening. Methods: YouTubeTM videos were investigated by relevance for the term “Teeth Whitening”. According to the inclusion criteria, 62 Turkish videos were evaluated. Data on the videos (number of views, video duration, number of likes, number of comments, viewing rate, video upload source, interaction index, and video power index) were determined. The reliability of the videos was evaluated with the Modified DISCERN (Mod DISCERN) scale, and their quality was assessed with the Global Quality Scale (GQS) scale. The Mann-Whitney U test and Spearman's rank correlation coefficient were utilized. Results: In terms of the video upload sources, 74.2% (n=46) of the videos examined were patients, and 25.8% (n=16) were physicians. The median values for likes, comments, viewing rates, views, and video duration for the videos uploaded by patients were found to be higher than those uploaded by physicians (P < .05). The GQS (P < .001) and Mod DISCERN (P < .001) scores were found to be significantly higher in the videos uploaded by physicians compared with the videos uploaded by patients. There was a high correlation between GQS and Mod DISCERN scores (r=0.929, P < .001).Conclusion: The information reliability and video quality of most videos shared on the YouTubeTM platform about teeth whitening are not sufficient. Internet users should be very careful when using information obtained from the internet on health-related issues.